Histological types and papillar growth patern in borderline ovarian tumors - Gorišek, Borut (Zdravniški vestnik, 2009)
Background. Our retrospective study was carried out with the aim of establishing the percentage of histologic types in borderline ovarian tumors (BLOT), bilateralism and the presence of papillary growth according to individual types. Methods. The study included 55 women treated at Maribor Teaching Hospital between January 1st, 1993 and December 31st, 2001. Data were collected up to April 1st, 2005. Results. Serous BLOT prevailed (74.5 %) while the number of mucinous BLOT was smaller (21.8 %). Borderline ovarian tumors were bilateral in 20 % of women and unilateral in 80 %. Among bilateral BLOT the serous type prevailed (90.9 %) while the mucinous were bilateral less often (9.1 %). Of the bilateral BLOT as many as 63.6 % were in stage II-IV. Papillary growth was found in 40 % of BLOT, 95.45 % of them were of the serous and only 4.45 % of the mucinous type. A statistically significant connection was established between the serous histologic type of BLOT and papillary structure (P = 0.004). Conclusions. Borderline ovarian tumors are mostly serous, one fourth are bilateral and more than one half have papillary growth. Serous BLOT involve peritoneal implants and positive pelvic lymph nodes more often than the mucinous. Mucinous BLOT were mostly unilateral, rarely with papillary growth, and with negative lymph nodes.
Keywords: classification; diagnosis; histologija; Jajčnik, novotvorbe; jajčniki; Klasifikacija; malignost; Neoplasms by Histologic Type; novotvorbe; Novotvorbe, histološki tip; Ovarian Neoplasms; Ovarij, novotvorbe; Papilloma; Papilom; pathology; Patologija; therapy; tumor; Ugotavljanje; Zdravljenje